Avaliação da utilização do mexilhão dourado (Limnoperna fortunei Dunker, 1857) na elaboração de farinha para alimentação da tilápia (Oreochromis niloticus Linnaeus, 1758) - Canzi, Carla (2011)
The study was conducted to know the nutritional value of the invasive mussel L. fortunei and its potential use as food in the manufacture of feed for fish. The work was done in two stages. The first step processed two types of meal, using a mussel in its integral form (valves and body content), called the FMI, and the other using only the valves and called FMV. In the processed materials analysis of crude protein (CP) were done, lipids, ash, calcium (Ca), phosphorus (P), Sodium (Na), Potassium (K), Lead (Pb), Cobalt (Co), Copper (Cu ), Mercury (Hg), Zinc (Zn), pH and bacteriology (Salmonella sp, bactérias mesófilas, enterobacterias e E. colli). In the second step the material was submitted to evaluate the apparent digestibility of CP, and availability of Ca and P, for Tilápia (Oreochromis niloticus). The results were: CP (%) 12.95 and 8.64; Lipids (%) 1.01 and 0.42, Ash (%) 80.53 and 86.43 (%) P (%) 0, 11 and 0.10, Ca (%) 27.27 and 28.70; Na (%) 3.79 e3, 29 and pH 6.7 and 6.9, for FMV and IMF, respectively. The results of heavy metals and bacteriology were considered acceptable for use in animal feed. Regarding the apparent digestibility of crude protein and apparent availability of Ca and P, the material did not show satisfactory performance and is not considered appropriate to use for feeding tilápia.